Emotion-gamified tools for blended and online courses (2016)
This document presents a proposal for using gamification in blended and online courses, including elements different from behavioral ones. These elements consider topics such as online courses, massive open online courses (MOOC), emotions, affective models and gamification, and show how some authors integrate these topics. The goal of this work is to define a system capable to include a user affective model, gamification and emotions elements and a rule based software to setup the use of these elements in a learning environment.